Ceylon along the rail track - Cave, Henry W. (Henry William), 1854-1913. (Boralesgamuwa : Visidunu Prakashakayo, 2002)
Description of Sri Lanka along its railroads.
Originally published: 1st ed. London ; New York : Cassell and Company, Ltd. under the title: The Ceylon government railway.
Includes index.
Keywords: Railroad travel -- Sri Lanka; Sri Lanka -- Description and travel